Analisis Kualitas Air Budidaya Ikan Lele Sangkuriang (Clarias gariepinus) di Kabupaten Manokwari, Papua Barat - Anggiat Sinaga; Syafrudin Raharjo; Vera Sabariah (Faculty of Agriculture Musamus University, 2021)
Sangkuriang catfish (Clarias gariepinus) a freshwater fish, that is well-known as aquaculture commodity in Manokwari Regency. Water quality is a determining factor for the success of catfish farming. The purpose of this study is to determine the dynamics of water quality and to determine the feasibility of catfish culture water quality in Manokwari Regency according to the required quality standards. The method used was descriptive by direct field data collection in Prafi and Masni Districts, which are known as catfish farming centers. The results showed that in the Prafi ponds temperature was 28 - 31 0C, pH: 6.8 – 7.56 and DO: 3.2 - 6.2 ppm and the Masni temperature 27 -31 0C, pH 6.62 - 7, 60 and DO: 3.2 – 7.1 ppm. Nitrate concentrations in the Prafi ponds ranged from 0.8 to 1 mg/l and in the Masni ponds from 0.7 to 1.2 mg/l. Ammonia concentrations in the Prafi and Masni ponds ranged from 0.06 to ≥ 0.5 mg/L. Temperature, pH, DO and Nitrate are in accordance to the required quality standards while Ammonia is not in accordance to the quality standards of Government Regulation Number 82/2001.